2018
DOI: 10.1177/1055665618757367
|View full text |Cite
|
Sign up to set email alerts
|

Active Presurgical Infant Orthopedics for Unilateral Cleft Lip and Palate

Abstract: Effects of active PSIO are multifaceted and intertwined with use of revision surgery. In our study, centers using either the Latham appliance combined with early revision surgery or the NAM appliance without revision surgery achieved better nasolabial aesthetic outcomes but worse maxillary growth, compared to a center using no PSIO and secondary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…Nasoalveolar molding-treated patients were found to have a comparable outcomes to non-NAM-treated patients from the same treatment center as well as from 2 other treatment centers, but worse outcomes than non-NAM-treated patients from a third center. Due to multiple differences in treatment protocols, the cause of these growth differences could not be determined (Kornbluth et al, 2018). Despite these difficulties, numerous published studies have detected no adverse effects in NAM-treated patients.…”
Section: Abstract Nonsyndromic Clefting Infant Orthopedics Facial Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasoalveolar molding-treated patients were found to have a comparable outcomes to non-NAM-treated patients from the same treatment center as well as from 2 other treatment centers, but worse outcomes than non-NAM-treated patients from a third center. Due to multiple differences in treatment protocols, the cause of these growth differences could not be determined (Kornbluth et al, 2018). Despite these difficulties, numerous published studies have detected no adverse effects in NAM-treated patients.…”
Section: Abstract Nonsyndromic Clefting Infant Orthopedics Facial Gmentioning
confidence: 99%
“…Published evidence shows that NAM-treated patients demonstrated improved anthropometric measures such as nasal tip projection (Peanchitlertkajorn et al, 2018) and nasal symmetry (unilateral cleft lip and palate [UCLP]; Barillas et al, 2009; Chou et al, 2017) and improved columellar length (Lee et al, 2008) and normalize nasal morphology (bilateral cleft lip and palate [BCLP]; Garfinkle et al, 2011; Meazzini et al, 2018). In addition to these objective differences, NAM treatment is also associated with subjective improvements in nasal aesthetics (Chang et al, 2010; Kornbluth et al, 2018).…”
mentioning
confidence: 99%
“…Nasoalveolar molding is a nonsurgical treatment performed during the first 3 to 5 months after birth, which utilizes an orthopedic appliance to reposition distorted alveolar segments, improve the shape of nasal cartilages, and enlarge or elongate relevant soft tissue structures to facilitate surgical repair. Nasoalveolar molding has been demonstrated to improve objective measures of nasal symmetry and morphology (Bennun et al, 1999; Barillas et al, 2009; Peanchitlertkajorn et al, 2018), improve subjective nasal aesthetics (Kornbluth et al, 2018), and to nearly eliminate the need for surgical nasal revisions in unilateral cleft lip and palate (Lee et al, 2008; Patel et al, 2015). In many cases, NAM may also facilitate the performance of gingivoperiosteoplasty (GPP) at the time of lip repair, which eliminates the need for future alveolar bone grafting in 60% to 75% of cleft sites (Santiago et al, 1998; Sato et al, 2008; Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although nasoalveolar molding has been widely adopted by many North American centers, 1,2 the literature regarding outcomes has been contradictory, and its use continues to be debated. [2][3][4][5][6] Studies have demonstrated favorable changes before and after nasoalveolar molding 7-12 and immediately after surgery [13][14][15] ; however, what is not clear is whether these changes are long lasting or…”
mentioning
confidence: 99%